The Effect of Liquidity, Profitability, and Firm Size on Dividend Policy in Infrastructure Companies on the Indonesia Stock Exchange: JEL Classification: G35, G32, G30, G10, L94 - Adrianus Saputra; Hartono Hartono (Newinera Publisher, 2025)
This study aims to analyze the influence of liquidity, profitability, and company size on profit sharing policy in infrastructure sector companies listed on the Indonesia Stock Exchange. This study uses an associative approach. The study population is infrastructure sector companies listed on the Indonesia Stock Exchange between 2020 and 2024. The sampling technique used is positive sampling, resulting in 20 companies. Data processing in this study used SPSS (Statistical Program for Social Sciences) version 26 software. Data analysis techniques were performed using classical assumption tests (normality, multicollinearity, heteroscedasticity, and autocorrelation), multiple regression analysis, the coefficient of determination test (